Impact of coronavirus on pregnant females in India: an observational study - Garg, Megha; Jain, Madhu; Jain, Shuchi (International Journal of Research in Medical Sciences, 2020)
Background: Coronavirus (COVID-19) has emerged as a rampant pandemic and the entire world is struggling against it. The entire nations are trying to device measure like national lockdowns, diverting resources towards fighting coronavirus, extensive media coverage, closing of elective services in hospitals. All this has influences the masses to a deep level. Coronavirus not only is morbid for the sick, but also the healthy pregnant females seeking health care and impacted them more mentally than physically. Methods: In this study 103 pregnant females from the entire nation of India were made to answer a well thought and made questionnaire which aimed at assessing the mental state and impact of coronavirus on the pregnant females. Results: Majority of the females answered that they felt anxious and were undergoing stress due to the coronavirus. They fear impending doom for the child and also are struggling a lot to seek apt healthcare for themselves and their children because of the ongoing pandemic. Conclusions: Coronavirus has not only affected people who are directly affected with the virus, but also who are still not affected but are mentally stressed because of it. National lockdown and alteration in the healthcare services are also stress- inducing for the pregnant females.